Inclusive education: How to upgrade from a “Technology Porter” to a “Demand Translator” - Ma Ying; Mohd Hussain, Rosila Bee (Jurnal Pendidikan Bitara UPSI, 2025)
This article adopts a comprehensive definition of disability, encompassing physical, sensory, mobility, and cognitive impairments, and extends the definition of technology to include various forms of online learning (both distance and blended), assistive technologies (AT) such as screen readers and alternative keyboards, general-purpose technologies like tablets and mobile phones, administrative applications including registration systems, social networking applications, and application-specific technologies such as statistical software. Over the past decade, technological advancements have progressed at a rapid pace, presenting both benefits and challenges for students with disabilities. On one hand, technology has the potential to assist individuals with disabilities in managing the complexities associated with their conditions, thereby facilitating social integration. Conversely, the adverse effects of technological shortcomings on disability education are often overlooked. This article investigates the interplay between technology and disability education through a qualitative study focused on this subject. The primary research question seeks to understand how technology can enhance the self-perception and educational experiences of individuals with disabilities, rather than merely serving as a means to accommodate their disabilities. The study aims to explore the perceptions, beliefs, and experiences of both disabled learners and educators regarding technology, assess their attitudes towards the implementation of specific technologies in educational contexts, and identify factors that may either hinder or promote inclusive education for individuals with disabilities. The article aspires to delineate a proactive approach to inclusive education for individuals with disabilities by analyzing the following four key points: • How can convenient technology be made widely accessible to ensure equal participation of all individuals with disabilities in social life? • De-standardization: In what ways can individuals with disabilities be empowered to exert control over technology? This control entails the ability to engage with technology at their discretion and to make as many independent decisions as possible, thereby fostering a sense of autonomy and independence that connects them to the broader community rather than isolating them. • Professional development for educators: How can technology be utilized to assist educators in evolving from mere "technical porters" to "demand translators," enabling them to provide more customized support for students with disabilities rather than adopting a mechanical approach? • Addressing emotional and practical needs: How can educators prioritize emotional and practical considerations in their support of individuals with disabilities, utilizing technology as a tool to address genuine needs rather than allowing technology to overshadow the human element of education?